2022
DOI: 10.1101/2022.01.31.478567
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fundamental limits of amplification-free CRISPR-Cas12 and Cas13 diagnostics

Abstract: Interest in CRISPR diagnostics continues to increase. CRISPR-Cas12 and Cas13 based detection are particularly interesting as they enable highly specific detection of nucleic acids. The fundamental sensitivity limits of Cas12 and Cas13 enzymes are governed by their kinetic rates and are critical to develop amplification-free assays. However, these kinetic rates remain poorly understood and their reporting has been inconsistent. We here measure kinetic parameters for several enzymes (LbCas12a, AsCas12a, AapCas12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Collectively these results suggest that the dsDNase activity of Cas12a2 is instrumental in triggering the Abi phenotype. Additionally, as a proof-of-principle demonstration, we show that Cas12a2 can detect RNA at a sensitivity comparable to that of RNA-targeting Cas13a nuclease at various temperatures 18 .…”
Section: Main Textmentioning
confidence: 78%
See 3 more Smart Citations
“…Collectively these results suggest that the dsDNase activity of Cas12a2 is instrumental in triggering the Abi phenotype. Additionally, as a proof-of-principle demonstration, we show that Cas12a2 can detect RNA at a sensitivity comparable to that of RNA-targeting Cas13a nuclease at various temperatures 18 .…”
Section: Main Textmentioning
confidence: 78%
“…Cas12a2 holds substantial potential for CRISPR technologies. As a proof-of-principle demonstration, we showed that SuCas12a2 can be repurposed for RNA detection with a limit of detection comparable to existing single-effector based tools 18 . Beyond the ability to detect RNA, we envision a variety of SuCas12a2 applications that expand and enhance the CRISPR-based tool kit.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A fluorescence calibration curve was then used to convert fluorescence values (in AU) to molar concentrations (in nM). 19,20 To this end, two nonlinear fits were performed on calibration data, one each for cleaved and uncleaved reporters ( Fig. S1 ).…”
Section: Methodsmentioning
confidence: 99%